Prison mediation as alternative dispute resolution between domestic prisons - Enrique Pastor Seller; Elena Huertas Perez (Sociedad Iberoamericana de Pedagogía Social, 2013)
<!--[if gte mso 9]> <![endif]--> Mediation is a method penitentiary peaceful resolution of internal conflicts based on dialogue and respect, allowing those involved to take responsibility for their behavior, the role in the process and the peaceful resolution of the conflict itself. The research center aims to demonstrate the viability of mediation in prisons for the alternative resolution of interpersonal conflicts among inmates. To do so, first, we analyze the institutional and legal mechanisms for resolving interpersonal conflicts in Spanish prisons. It then proceeds to characterize the prison population from a comparative analysis, identifying, likewise, services and / or existing mediation projects and, finally, discusses, from its participants, conflicts and feasibility of using mediation in Specifically a Penitentiary. For the realization of the research have been used primary and secondary sources, with both quantitative and qualitative. The results of the investigation confirm that mediation is feasible and effective in the prison setting. <!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="72" SemiHidden="false" UnhideWhenUsed="false" Name="Colorful List